2010
DOI: 10.1248/bpb.33.1555
|View full text |Cite
|
Sign up to set email alerts
|

Vasorelaxant Activity of Sappan Lignum Constituents and Extracts on Rat Aorta and Mesenteric Artery

Abstract: We investigated the vasorelaxant activity of the methanolic extracts of Sappan Lignum (CSE) and its constituents, brazilin, sappanchalcone, and protosappanins A-E, on rat aorta and mesenteric artery. By comparing the vasorelaxant activity of CSE and brazilin on both blood vessels, we found that CSE contained active constituents other than brazilin. When added to brazilin, sappanchalcone and protosappanin D showed vasorelaxant activity on both blood vessels precontracted with phenylephrine. We clarified that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…14,16,18) Measurement of Isometric Force Measurement of the isometric force was performed as described previously. 7,[14][15][16][17][18][20][21][22][23][24][25] Mice were anesthetized with 5% isoflurane and sacrificed by decapitation. The thoracic aortas were removed from mice and put in Krebs-Henseleit Solution (KHS) (consisted of KHS (mmol/L); 118.0 NaCl, 4.7 KCl, 25.0 NaHCO 3 , 1.8 CaCl 2 , 1.2 NaH 2 PO 4 , 1.2 MgSO 4 , and 11.0 glucose) and cut from perivascular fat carefully.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…14,16,18) Measurement of Isometric Force Measurement of the isometric force was performed as described previously. 7,[14][15][16][17][18][20][21][22][23][24][25] Mice were anesthetized with 5% isoflurane and sacrificed by decapitation. The thoracic aortas were removed from mice and put in Krebs-Henseleit Solution (KHS) (consisted of KHS (mmol/L); 118.0 NaCl, 4.7 KCl, 25.0 NaHCO 3 , 1.8 CaCl 2 , 1.2 NaH 2 PO 4 , 1.2 MgSO 4 , and 11.0 glucose) and cut from perivascular fat carefully.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Previous reports showed that the extracts of C. sappan L. could exert vasorelaxant activity and anti-inflammation activity (Washiyama et al, 2009;Sasaki et al, 2010). Particularly, protosappanin A (PTA) and protosappanin B (PTB) are two representative dibenzoxocin derivatives from C. sappan L. (Lu et al, 2013;Tong et al, 2013) and own the same molecular core structure.…”
Section: Introductionmentioning
confidence: 99%
“…Although NO is expected to be intimately involved in Oketsu, few studies have investigated this relationship, especially in vivo [7–9]. We previously reported that Kangenkaryu, an anti-Oketsu reagent, increased NO metabolites and affected the NO-superoxide balance in humans [10].…”
Section: Discussionmentioning
confidence: 99%